Integrative Model of Islamic Boarding School and Formal School Education in Producing a Superior Generation - Sholehuddin, Sholehuddin; Abdul Rohman, Maskuri; Wahyudin, Aji; Hidayatur Rohman, Ahmad Taufiq; Khidhir Jovani, Ahmad Fernando (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
This study aims to explore Islamic Boarding Schools in Indonesia that has undergone significant transformation in the era of globalization, where they not only function as traditional religious educational institutions but also begin to integrate formal education systems into their curriculum. This integration aims to provide students with a deep understanding of religion without neglecting academic skills relevant to the development of the times. This study focuses on the analysis of collaboration between Islamic boarding schools and formal educational institutions, which is expected to improve the quality of students in terms of academics and character. The learning model that combines religious education with formal education has produced a competent generation both academically and spiritually. This study delves deeper into the strategy of curriculum integration, time management, and communication between Islamic boarding schools and formal schools. The results show that this model not only improves students' academic abilities but also strengthens their character and spirituality so that they can compete in the global world without losing Islamic values. Therefore, this study offers strategic recommendations to optimize curriculum integration between Islamic boarding schools and formal educational institutions and develop a more inclusive, adaptive, and sustainable education model to face the challenges of globalization.